A Critical Ethnography of Outreach Nursing for People Experiencing Homelessness. Issue 4 (1st October 2020) - Paradis-Gagné, Etienne; Pariseau-Legault, Pierre; Villemure, Midori; Chauvette, Simon
ABSTRACT: People experiencing homelessness have a high prevalence of substance abuse and mental and physical problems. Although they have very complex health needs, they face many barriers that reduce their access to health care and social services. Several research studies have shown the need to implement adapted nursing interventions to address these crucial access issues. In this article, we present the results of a critical ethnography of outreach nurses who work with homeless people (n = 12). Robert Castel's theoretical model, which focuses on the process of social disaffiliation, provided the conceptual underpinnings for this research. Our qualitative data analysis revealed four categories, namely 1) the professional role and identity of nurses; 2) the social function of outreach nursing; 3) clinical realities and 4) disaffiliation and stigmatization. Our findings highlight the need to raise awareness among health care providers about the ethical, clinical and organizational issues of homelessness, particularly the mechanisms of exclusion and stigmatization in health care settings that affect people experiencing homelessness.